2005
DOI: 10.1146/annurev.biophys.34.040204.144534
|View full text |Cite
|
Sign up to set email alerts
|

Use of EPR Power Saturation to Analyze the Membrane-Docking Geometries of Peripheral Proteins: Applications to C2 Domains

Abstract: Despite the central importance of peripheral membrane proteins to cellular signaling and metabolic pathways, the structures of protein-membrane interfaces remain largely inaccessible to high-resolution structural methods. In recent years a number of laboratories have contributed to the development of an electron paramagnetic resonance (EPR) power saturation approach that utilizes site-directed spin labeling to determine the key geometric parameters of membrane-docked proteins, including their penetration depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 42 publications
4
82
1
2
Order By: Relevance
“…Recently, electron paramagnetic resonance ( 44,54,55 ) and X-ray refl ectivity ( 45 ) studies have elucidated the cPLA 2 ␣ -C2 domain orientation in the presence of POPC lipids; however, the orientation when C1P is present in the membrane is still unknown. We found that starting with the same orientation ( 44 ) as that with only POPC, the domain tilts by ‫ف‬ 10° toward the bilayer over the course of the simulation in the presence of C1P ( Fig.…”
Section: An Experimental Analysis Of Cpla 2 ␣ -C2 and C1p Interactionsmentioning
confidence: 99%
“…Recently, electron paramagnetic resonance ( 44,54,55 ) and X-ray refl ectivity ( 45 ) studies have elucidated the cPLA 2 ␣ -C2 domain orientation in the presence of POPC lipids; however, the orientation when C1P is present in the membrane is still unknown. We found that starting with the same orientation ( 44 ) as that with only POPC, the domain tilts by ‫ف‬ 10° toward the bilayer over the course of the simulation in the presence of C1P ( Fig.…”
Section: An Experimental Analysis Of Cpla 2 ␣ -C2 and C1p Interactionsmentioning
confidence: 99%
“…A number of creative approaches are now being applied to fill in the gaps. The application of site-specific labeling for fluorescence resonance energy transfer (FRET) and electron paramagnetic resonance (EPR; [23] and see Cafiso chapter) was pioneered in studies of C2 domain:membrane interactions. These techniques now appear to be mature enough to be applied to other membrane-binding domains and perhaps to larger membraneassociated assemblies nucleated by these domains.…”
Section: Archetypal Lipid Binding Domainsmentioning
confidence: 99%
“…A computational electrostatic model has been developed that appears to explain the observed specificity differences through changes both in interaction energies and in the penalty for desolvating charges near the membrane [42]. Considerable effort has gone into defining the geometry of C2 domain interactions with membranes, making this field a test bed for applying FRET, EPR, x-ray reflectivity, and computational methods ( [23]; Cafiso chapter).…”
Section: C2 Domainsmentioning
confidence: 99%
“…Biochemical and biophysical studies over the past 2 decades have provided considerable insight into the structure and function of C2 domains (9,(15)(16)(17). The C2 domain is an ϳ130 residue segment that folds into two four-stranded ␤-sheets using one of two different topologies, depending on the protein (15).…”
mentioning
confidence: 99%